FACTORS RELATED TO NUTRITIONAL CHILDREN IN GUNUNG KALER PUSKESMAS, TANGERANG REGENCY - Siti Masitoh; Nanik Yuliwati (International Journal of Medicine and Health, 2022)
The prevalence of underweight in 2018 in Indonesia is 17.7%, consisting of 3.9% malnutrition and 13.8% malnutrition. Banten is one of the sixteen provinces in Indonesia showing a prevalence of underweight, where in 2016 the number of malnutrition in toddlers reached 1051 toddlers spread in 8 cities / regencies in Tangerang, Banten, in 2017 the number of malnutrition in toddlers was 74 toddlers. The Research Objectives is To find out the factors that are related to underweight status in children under five at Gunung Kaler Health Center, Tangerang Regency, Banten Province. Descriptive correlative study with case control approach. The sample in this study were toddlers at Gunung Kaler Health Center as many as 58 under five malnourished children and 58 under-fives with good nutrition taken by purposive sampling technique. Data was obtained by distributing questionnaires and measuring nutritional status. Data analysis using univariate and bivariate with chi-square test. The Results is There is a relationship between maternal knowledge (Value = 0,000; OR = 5,884), family income (Pvalue = 0.002; OR = 3,709), parenting style (Pvalue = 0,000; OR = 6,331), infectious disease (Pvalue = 0,000; OR = 4,222) with nutritional status of toddlers. Conclusions and Suggestions of this research are Mother's knowledge, family income, upbringing and infectious diseases are associated with poor nutritional status in toddlers. Puskesmas increase the frequency of counseling for mothers who have toddlers in particular. Besides that, there was a knock on door program by following up toddlers with under-nutrition status.